2005
DOI: 10.1111/j.1439-0507.2005.01124.x
|View full text |Cite
|
Sign up to set email alerts
|

Candidal overgrowth in diabetic patients: potential predisposing factors

Abstract: This study was designed to investigate the potential factors that influence the prevalence of the oral carriage of Candida species in patients with type II diabetes mellitus. One hundred and twenty-eight diabetic patients (68 males and 60 females, mean age 54 +/- 7 years) were sequentially enrolled along with 84 (44 males and 40 females mean age 52 +/- 8 years) healthy subjects. Samples were obtained by swabbing the oral mucosa of all participants. Yeast isolates were identified by germ tube test, with API 32 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
113
2
6

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 126 publications
(144 citation statements)
references
References 26 publications
12
113
2
6
Order By: Relevance
“…In the 15 studies that employed controls, only half showed a statistically significant increase in the carriage of C. albicans in diabetes, and there was a variable relationship between salivary glucose and oral carriage [68]. Between-study differences are likely to reflect methods of selection of diabetic subjects and controls, sampling techniques, and perhaps also group differences in putative aetiological factors such as denture wearing and xerostomia [70].…”
Section: Skin Nail Mucous Membrane and Soft Tissue Infectionsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the 15 studies that employed controls, only half showed a statistically significant increase in the carriage of C. albicans in diabetes, and there was a variable relationship between salivary glucose and oral carriage [68]. Between-study differences are likely to reflect methods of selection of diabetic subjects and controls, sampling techniques, and perhaps also group differences in putative aetiological factors such as denture wearing and xerostomia [70].…”
Section: Skin Nail Mucous Membrane and Soft Tissue Infectionsmentioning
confidence: 99%
“…In clinical studies, however, findings have been inconsistent. In a recent review of 21 studies [70], oral carriage rates in diabetic subjects ranged from 18 to 80%. In the 15 studies that employed controls, only half showed a statistically significant increase in the carriage of C. albicans in diabetes, and there was a variable relationship between salivary glucose and oral carriage [68].…”
Section: Skin Nail Mucous Membrane and Soft Tissue Infectionsmentioning
confidence: 99%
“…8 Number of colonies contained in 50 μl of saliva = n Therefore the number of colonies in 1000 μl (1 ml) = n x 1000/50 = n x 20…”
Section: Methods Of Counting Coloniesmentioning
confidence: 99%
“…8 Dehydration associated with elevated blood glucose increases osmotic gradients within the salivary glands, thereby limiting secretion. 10,23 Autonomic neuropathies that diminish the ability of salivary glands to respond to a salivary stimulus or microvascular changes that compromise the ability of salivary glands to respond to neural or hormonal stimulation in diabetic patients could explain the significantly lower salivary flow rates in diabetics.…”
mentioning
confidence: 99%
“…It is associated with reduced salivary pH and facilitates oral candidal overgrowth and colonization. [7] As an opportunistic infection, oral candidiasis is also associated with a wide spectrum of systemic dis--eases that suppress the host auto--immunity [8].…”
Section: Denture Wearingmentioning
confidence: 99%